Numerical Model for High Relative Capacity of Tensegrity Cable Domes - Nacer LOGZIT; Khelifa KEBICHE (Civil Engineering Dimension, 2020)
The tensegrity cable domes are a type of structures composed of compressed bars and tensioned cables. They are characterized by an exceptional innovation in terms of lightness. Research in this area is booming towards multiple applications. In the absence of an approach linking design by dimensioning, this article aims to propose a procedure for verifying the design while seeking a better lightness of the structure. The article uses the novelty of the methods applied for this kind of structure, using the hypothesis of geometric nonlinearity, to find the best solution, verifying all the sizing criteria. Through an example of a simple cables dome, we have shown the feasibility of this approach. The shape of the triangles forming the basis of design, have a direct relationship on the relative capacity, this last has been significantly improved, This method can easily be applied to other examples of more complex cables domes.